Content coverage in local government authority websites in Tanzania: a web content analysis - Mtega, Wulystan Pius (University of Dar es Salaam Library Journal, 2020)
This study assessed the content coverage on local government authority websites in Tanzania to establish an understanding of their ability to serve as useful platforms for informing and communicating with the public. Specifically, the study has determined the thematic areas covered by web contents, identified the forms and types of web contents, and determined the intended audience and aims of the web contents on local government authority websites. Content analysis was used to determine the presence of certain words, themes, or concepts within the 11 randomly selected local government authority websites. The study ' s findings indicate that content coverage on local government authority websites is very low. Moreover, most of the web contents were in less rich media and were specifically for providing news and alerts on current events rather than providing knowledge and complementing experts in the provision of services to local communities. The study concludes that with the low level of content coverage, local government authority websites cannot serve as one-stop information centres. It is recommended that local government authorities should generate more web contents for complementing their services rather than concentrating on news provision.